Re-read Hadith of Prophet Muhammad in the Context of LGBT: Intertextual Study on Dynamics of Islamic Law and Human Right - Hi. Abdul Qayum, Abdul Rahman; Miftahuddin, Miftahuddin; Ulfazah, Yernati; S Puyu, Darsul; Ahmad, La Ode Ismail (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2025)
The study aims to understand the interpretation of relevant Hadith texts in modern contexts, in light of the growing debate over LGBT rights and social acceptance among Muslim communities. The study uses qualitative research methods with the analysis of Hadit texts related to sexual behavior and morality, as well as interviews with scholars. The results of research show that the practice of LGBT people in the Hadith of the Prophet is called a fahisyah because, out of the human fitrah, their respective identities have been embedded. According to fiqh scholars, LGBT practices are unlawful, and the perpetrators must be given strict penalties in accordance with the gravity of the acts committed. In a social and cultural approach, LGBT practices can be accepted on the one hand by considering the human rights aspects and the principles of tolerance and the preservation of peace and well-being, but on the cultural side, people are alien to such practices because they have never been found in the tradition of traditional Muslim society or Indonesian society in general. In Islamic psychology, LGBT practices are mental illnesses caused by the domination of angry impulses, so that the tendency to make mistakes becomes greater and to deny things of a good nature. In health science, LGBT practices are becoming one of the biggest infectious causes of deadly diseases such as HIV/AIDS, gender diseases, and other contagious diseases. Thus, LGBT practices are still becoming a barrier to practice in Indonesian society, which is still traditional and adheres firmly to Islamic principles.